EU energy law and policy a South European perspective ; meeting the challenges of a low carbon economy - Hancher, Leigh 1956-; Metaxas, Antōnēs 20./21. Jh (Claeys & Casteels, 2017)
This book provides an insight into some of the most significant issues presented at the Florence School of Regulation and Hellenic Energy Regulation Institute's joint conference on European energy law and policy, which took place in September 2016 in Athens, Greece. The purpose of the conference was to provide a comprehensive analysis of the current status of the European Greek energy sector, and the issues it faces, from both a legal and economic perspective. The discussions included an assessment of the low carbon challenges for Europe, examining the future of renewable energy systems and support mechanisms, electricity market design, and the current regulatory framework of the gas and electricity markets in Greece. Finally, the discussions turned to the future role of Distribution System Operators, both in their function as independent supervisors of the electricity market and their evolving relationship with the Transmission System Operators
Includes bibliographical references
Keywords: Carbon dioxide mitigation / Law and legislation / fast / (OCoLC)fst01766586; Energy policy / fast / (OCoLC)fst00910200; Power resources / Law and legislation / fast / (OCoLC)fst01074312; Energy policy -- European Union countries; Power resources -- Law and legislation -- European Union countries; Carbon dioxide mitigation -- Law and legislation -- European Union countries; Carbon dioxide mitigation; Energy policy; Power resources; Europe / European Union countries / fast / (OCoLC)fst01269470; Europe